Evaluation of capacity and number of gates for delays and fuel consumption in the FTSP UII parking area - Hadi, Muhamad Abdul; Bintang, Muhammad Kennyzyra; Geovani Firdaus, Ad Zulfa; Farza, Ghina Hanifah (Journal of Engineering and Applied Technology, 2023)
One of the goals of campus development is to provide more adequate facilities for campus residents. This is caused by the increase in vehicles and a large traffic movement that will result in parking users having difficulty parking and causing congestion. This study was devoted to examining the capacity of the FTSP UII motorcycle parking area. Data in this study was obtained by conducting a survey at the research location. The research results will be obtained by comparing the capacity of the FTSP UII parking area in the existing conditions and the next 5 years as well as comparing the value of fuel consumption. Based on the research that has been carried out, the existing parking lot can still accommodate vehicles. Furthermore, in the next 5 years, the parking lot can no longer accommodate vehicles. In addition, it can be concluded that the addition of parking gates can reduce the queue length by 56%, delay by 19%, and fuel consumption by 19%.